Death-is-life-enhancing: Adaptation and validation of the Norwegian Death Mindsets Measure (NDMM). - Chang, Michelle; Thimm, Jens C. (Death Studies, 2025)
While existing psychological frameworks and their accompanying measures focus on death as anxiety-inducing and debilitating, we highlight an overlooked perspective of death—that death can be a basis for living with more meaning and presence. The present research adapts and validates the Death Mindsets Measure (DMM), which assesses the mindset that "death-is-life-enhancing," for a Norwegian context. Firstly, we translated the DMM and consulted with Norwegian bereavement experts and bereaved Norwegians on items' clarity and relevance to cultural perspectives of death. Secondly, we validated the Norwegian DMM (NDMM) on a predominantly bereaved community sample of Norwegians (N = 241). Using structural equation modeling, we confirmed the hierarchical two-factor structure of our measure. The NDMM also demonstrated high internal consistency and discriminant validity with existing death anxiety and death attitudinal measures. Finally, our measure explained additional variance in psychological well-being beyond existing death anxiety and attitudinal measures.